The fractal geometry of winter monsoon clouds over the Indian region (MAUSAM, 1990)
The fractal dimension of winter monsoon (October-: December) clouds over the Indian region during the 3 years 1985 to 1987 were determined from INSAT-I B cloud pictures using Lovejoy’s (1982) relationship P ~ÖAD  where , P, A and D are respectively the perimeter, area and the fractal dimension of the cloud.             The cloud study clearly indicates self-similar fractal structure to clouds of all sizes up to .the available maximum areal extent of about 5 x 106 sq km. The mean value of the fractal dimension of cloud perimeter is found to be equal to 1.30.